2021
DOI: 10.1007/s10694-020-01058-x
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Evacuation Behaviour in Retirement Facilities: Case Studies from New Zealand

Abstract: Ageing populations are generating new challenges for the safe design of buildings and infrastructure systems in communities around the world. Elderly building occupants are more likely to have mobility impairments, and in turn, require longer times and increased assistance to evacuate buildings compared with able-bodied adults. To date, only a few studies have been carried out to assess the evacuation performance of elderly evacuees in retirement homes. Therefore, it is necessary to collect critical evacuation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…It is seen that there was only one evacuee with a speed above 1.8 m/s, which is highlighted as an outlier. In line with previous studies, 17,29,51 F I G U R E 6 Pre-evacuation time distributions The unimpeded average stair walking speed was 0.97 ± 0.36 m/s, whereas the minimum and maximum speeds were 0.059 m/s and 1.24 m/s, respectively. These minimum and maximum speeds are also two common speeds of the majority of evacuees, which can be attributed (in part) to the short distance used to measure the speed.…”
Section: Evacuation Speedsupporting
confidence: 88%
See 1 more Smart Citation
“…It is seen that there was only one evacuee with a speed above 1.8 m/s, which is highlighted as an outlier. In line with previous studies, 17,29,51 F I G U R E 6 Pre-evacuation time distributions The unimpeded average stair walking speed was 0.97 ± 0.36 m/s, whereas the minimum and maximum speeds were 0.059 m/s and 1.24 m/s, respectively. These minimum and maximum speeds are also two common speeds of the majority of evacuees, which can be attributed (in part) to the short distance used to measure the speed.…”
Section: Evacuation Speedsupporting
confidence: 88%
“…It is seen that there was only one evacuee with a speed above 1.8 m/s, which is highlighted as an outlier. In line with previous studies, 17,29,51 a normal distribution was used to fit the horizontal speed data. The results are given in Table 4, showing a good fit with the data ( R 2 > 0.90).…”
Section: Resultsmentioning
confidence: 93%
“…One interpretation of these results is that participants who are elderly or have disabilities face additional challenges egressing from buildings (e.g., Hostetter & Naser, 2022;Rahouti et al, 2021;Oswald, 2021) and may be required to stay put to some extent because their personal emergency evacuation plans require them to wait for assistance from others before evacuating. While previous research has demonstrated that trust in safety procedures can influence the perception of risk by vulnerable persons (e.g., Tancogne-Dejean & Laclemence, 2016), the current study extends this to show that the perceived ability to adhere to the stay put guidance predicts both views of the guidance and also the creators of the guidance.…”
Section: Discussionmentioning
confidence: 99%
“…Scholars have been studying pedestrian simulation in emergencies and have developed various theories of group behavior [ 7 ]. During emergency evacuation, pedestrian response is not random movement, but rather a result based on individual social characteristics.…”
Section: Related Workmentioning
confidence: 99%
“…In the case of public safety emergencies, improper pre-evacuation decisions may cause escapees a delay in escape opportunity or a wrong choice of escape route [ 5 , 6 , 7 ], which are among the main factors in building casualties. Building environment and crowd behavior are closely related.…”
Section: Introductionmentioning
confidence: 99%